Management of chemical injury with total corneal scar and cicatrization treated with simple limbal epithelial transplantation and amniotic membrane transplantation: a case report - Suram, Sushma; Hood, Mitesh Mohan (International Surgery Journal, 2025)
Chemical injuries to the eye are medical emergencies that can result in severe visual impairment or blindness, especially when complicated by limbal stem cell deficiency (LSCD) and cicatrization. Simple limbal epithelial transplantation (SLET) combined with amniotic membrane transplantation (AMT) has shown promise in treating such conditions, offering a path to restore corneal clarity and function. A 46-year-old male presented with sudden vision loss, redness, and pain in the left eye following a chemical injury. Examination revealed a total corneal scar with cicatrization, and the patient was diagnosed with LSCD. He underwent SLET combined with AMT for corneal restoration. Postoperatively, gradual corneal clarity was observed, and vision improved to counting fingers at 2 meters, though further improvement was limited due to a cataract. This case underscores the potential effectiveness of SLET + AMT in managing severe chemical injuries complicated by LSCD. While partial recovery was achieved, further surgical intervention for cataract removal may be necessary to optimize visual acuity. The case highlights the importance of early diagnosis and timely surgical management in such patients.